Complexes of Oxovanadium(IV), Dioxouranium(VI) and Zirconium(IV) with Schiff Bases Derived from 2,2´ -Diamino-Diphenyl-Disulphide - Prabhu, P.M.; Mehta, B.H. (Asian Journal of Chemistry, 2010)
Six complexes of vanadium, uranium and zirconium have been synthesised using Schiff bases derived from 5-nitro-salicylaldehyde, 2-hydroxy-1-naphthaldehyde and 2,2´-diamino-diphenyl-disulphide. The complexes are chracterized by elemental analysis, magnetic measurements, UV/visible absorption spectra, infrared spectral, diffused reflectance spectra and conductance measurements. Thermogravimetric analysis played a supporting role to picturise the geometrical structures of the complexes.